Bidragsydere 22 - Rykind-Eriksen, Kirsten; Kröner, Ditte (Dragtjournalen, 2024)
Karis Silkjær Rasmussen Morten Grymer-Hansen Trine Skødt Viktor Benedict Heegaard Anna Toftgaard-Hansen Ulrik Reindel Tove Engelhardt Mathiassen Sussanne Klose Camilla Luise Dahl Ditte Kröner Kirsten Rykind-Eriksen